First-time homebuying: attitudes and behaviors of low-income renters through the financial crisis. Issue 8 (17th November 2017) - Lindblad, Mark R.; Han, Hye-Sung; Yu, Siyun; Rohe, William M.
Abstract: We use psychological theory to investigate how attitudes toward homebuying relate to first-time home purchases over the past decade. Homeownership rates in the US have dropped to 20-year lows, but whether views toward homebuying shifted due to the financial crisis is not known because studies have not compared attitudes for the same respondents pre- and post-crisis. We address this gap with 2004–2014 panel data from low-income renters. We find that a negative shift in homebuying attitudes is associated with a decline in first-time home purchases. Older renters aged more than 35 years at baseline report the greatest declines in homebuying intentions. Younger renters aged 18–34 also report diminished homebuying intentions, yet express highest overall levels of homebuying intentions pre- and post-crisis. Blacks report greater homebuying intentions although their odds of home purchase are 29 per cent lower than whites. Homebuying norms and favorability are associated with homebuying intentions but not with actual purchases, while perceived control over homebuying influences both outcomes.